Use of probiotics and reduction of pododermatitis in broiler chickens - Frozza, Rogerio; Inoue, Alberto; Jacinto, Andressa; Mello, Erico Adriani; Correia de Lima Almeida Paz, Ibiara; Lobo, Lucas Lopes Arrochela; Andrade, Marlon Guzzi de; Gomide, Sergio (Pubvet, 2024)
Pododermatitis lesions, also known as “foot calluses”, cause pain and discomfort, alter behavior and walking patterns, and can increase aggression among birds, thus compromising animal welfare. The disease also compromises bird performance, as it commonly results in a worsening of feed conversion and an increase in carcass condemnation. Other obstacles include failure to meet the consumer market for chicken feet, especially in Asia, and possible penalties in animal welfare audits. Numerous factors predispose the emergence of this lesion, such as environmental quality, management, litter quality and humidity, as well as the presence of ammonia (NH3). The present study evaluated the probiotic efficiency based on Bacillus subtilis and Bacillus licheniformis, GalliPro® MS, in reducing broilers’ incidence of pododermatitis (foot calluses). Chickens that received diets supplemented with GalliPro® MS had more intact paws, probably because the levels of NH3 and Nitrogen (N) in the litter were lower, ensuring a favorable microenvironment and maintaining the integrity of the paws.